Long-term toxicity following acute administration of nickel - Novelli, E. L B [UNESP]; Novelli Filho, J. L V B [UNESP]; Rodrigues, N. L. [UNESP]; Ribas, B. O.; Barbosa, L. L. (My University, 1998)
Nickel compounds have high potential risk for the health of populations and for this reason their toxic effects should be urgently established. To determine the effect of nickel monosulfide in the muscle at the injection site on pancreatic, hepatic, and osteogenic lesions and the potential therapeutic effect of Cu-Zn superoxide dismutase (SOD), male Wistar rats received single intramuscular injections of nickel monosulfide (NiS - 7 mg Ni2+/Kg). A group of these experimental rats were injected intraperitoneally, with a single weekly dose of SOD covalently linked to polyethylene glycol (SOD-PEG). Rats were sacrificed at 2, 4, 6, and 8 months after Ni2+ injection. Nickel monosulfide produced tumors at the injection site. The increased phospholipid, alanine transaminase (ALT), alkaline phosphatase (ALP), and amylase levels in serum, in absence of SOD-PEG, reflected the toxic effects on pancreatic, hepatic, and osteogenic tissues of rats. SOD activity was increased in serum of rats receiving SOD-PEG throughout the experiment, and no significant difference was observed in biochemical parameters of control and experimental rats in presence of SOD- PEG. Superoxide radical generated by Ni2+ is of primary importance in the development of tumors at the injection site. Superoxide anion (O2 -) is also an important toxic intermediate with respect to hepatic, pancreatic, and osteogenic injury, since SOD-PEG has a potential therapeutic effect.
Keywords: Intramuscular; Nickel monosulfide; Rats; Superoxide radical; Tumor; alanine aminotransferase; alkaline phosphatase; amylase; copper zinc superoxide dismutase; glutathione peroxidase; macrogol; malonaldehyde; nickel subsulfide; phospholipid; superoxide; animal experiment; animal model; animal tissue; bone injury; carcinogenesis; chelation therapy; chronic toxicity; controlled study; covalent bond; enzyme activity; health hazard; injection site; intramuscular drug administration; intraperitoneal drug administration; liver injury; male; muscle tumor; nonhuman; pancreas injury; rat; Animalia; Rattus norvegicus